(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Ulcerative colitis is a chronic inflammatory disease, and patients would get benefit more if the drug is given directly to the colon. Mesalazine is intended to deliver to the colon for treating ulcerative colitis. Here, we aimed to design and optimize mesalazine 400 mg delayed release tablet for colon-specific delivery using a quality by design (QbD) approach. The tablet was first formulated as an optimized core tablet and then coated with Eudragit S 12.5 for ensuring colonic delivery. The experimental design for the core tablet was constructed using a 32 full factorial design, where the percentages of sodium starch glycolate (SSG) and polyvinylpyrrolidone (PVP K-30) were independent variables and the tablet hardness (kg/cm2) and cumulative percentage of drug release at pH 7.2 phosphate buffer after 1.5 hours were treated as responses. Responses obtained from the initial exploratory formulations were evaluated to develop an optimized formulation to have a hardness value of 7-8 kg/cm2 and the maximum amount of drug release at pH 7.2 buffer. The optimized formulation involved the use of SSG and PVP K-30 at 3.05% and 1.69%, respectively. Hardness and cumulative percent of drug release obtained for the optimized core tablet were 7.8 kg/cm2 and 91.76%, respectively. The compatibility of drug and excipients was studied utilizing XRD, FTIR and TGA. The optimized core tablet was then coated with Eudragit S 12.5 to deliver the drug selectively to the colon and further assessed for its in vitro dissolution. Dissolution studies indicated that coated tablets with a weight gain of 7.4% exhibited the maximum cumulative percent of drug release (91.19 ± 0.11%), with a zero-order drug release profile (R2 = 0.943). A stability study performed according to ICH Q1A (R2) guidelines at accelerated storage conditions identified that there was no significant change in drug content over the storage period, indicating the stability of the formulated tablet batches. Together, these data suggest that the mesalazine tablet developed through the QbD approach offers excellent physical properties and drug release profile and, therefore, could be recommended for commercial manufacturing. Dhaka Univ. J. Pharm. Sci. 22(2): 189-201, 2023 (December)